Comparative Analysis of Broiler Chicken Farming Business Income Partnership Pattern and Independent Pattern in Sungai Ambawang District, Kubu Raya Regency - Heraini, Dela; Pambudi, Ramadhan Luhur; Tohardi, Ahmad (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
Poultry business has a strategic value in meeting animal protein in Kubu Raya Regency, especially broiler chicken types, in both partnership and independent patterns. This study aims to determine the income comparison between broiler chicken farmers who carry out partnership and independent patterns in Sungai Ambawang District, Kubu Raya Regency. This type of research is a collective case study research, namely examining cases related to cost components to determine and compare the amount of income of broiler chicken business types, partnership, and independent patterns. The results of the study showed that the total variable cost of the independent pattern was IDR 1,519,400,000, and the partnership pattern was IDR 1,490,620,000. The total production cost of the independent pattern was IDR 1,519,400,000, and the partnership pattern was IDR 1,490,620,000. The amount of income from the independent pattern was IDR 1,580,087,500, and the partnership pattern was IDR 1,536,747,500. It can be concluded that the independent broiler chicken farming business is more profitable than the partnership chicken farming business.